Exosomes Derived From miR-133b-Modified Mesenchymal Stem Cells Promote Recovery After Spinal Cord Injury - Li, Dong; Zhang, Peng; Yao, Xiyang; Li, Haiying; Shen, Haitao; Li, Xiang; Wu, Jiang; Lu, Xiaocheng (Frontiers in Neuroscience, 2018)
Dysregulation of microRNAs (miRNAs) has been found in injured spinal cords after spinal cord injury (SCI). Previous studies have shown that miR-133b plays an important role in neuronal differentiation and neurite outgrowth. Recently, exosomes have been used as novel biological vehicles to locally or systemically transfer miRNAs, but little is known about the effect of exosome-mediated miRNA delivery on the treatment of SCI. In the present study, we observed that mesenchymal stem cells, the most common cell types known to produce exosomes, could package miR-133b into secreted exosomes. After SCI, tail vein injection of miR-133b exosomes into rats significantly improved hindlimb functional recovery when compared to control groups. Additionally, treatment with miR-133b exosomes reduced lesion volume, preserved neuronal cells, and promoted axonal regeneration after SCI. We next observed that the expression of RhoA, a direct target of miR-133b, was decreased in the miR-133b exosome group. Moreover, we showed that miR-133b exosomes activated ERK1/2, STAT3, and CREB, which are signaling pathway proteins involving neuronal survival and axonal regeneration. In summary, these findings demonstrated that systemic injection of miR-133b exosomes preserved neurons, promoted axonal regeneration, and improved hindlimb locomotor recovery following SCI, suggesting that exosome-mediated miRNA transfer represents a novel therapeutic approach for the treatment of SCI.